Spatial variation in energy attitudes and perceptions: Evidence from Europe - Balta-Ozkan, Nazmiye; Le Gallo, Julie (Elsevier, 2017)
Driven by socio-economic processes, the influence of spatial factors on household energy related attitudes and perceptions is largely neglected in the literature. This paper analyses the extent to which energy perceptions and attitudes vary across different geographical contexts in Europe. We use representative Eurobarometer survey data to analyse how social conceptions of important energy issues, Europe's future energy priorities, and future energy system characteristics are shaped by rural, small urban, and large urban contexts. Using binary and ordered probit models, we find that householders in large and small areas are less likely to think of energy as a nationally important issue compared to their rural counterparts. Large city residents are less likely to think that renewables will play a significant role in the future energy system. Residents of large urban areas are more likely than those in rural areas to think that national energy policy should be centred on protecting the environment, guaranteeing a continuous supply of energy, and less around guaranteeing low prices for consumers.
Keywords: Energy attitude; Energy geography; Urban energy; Rural energy; Energy perception